Analysis of Evaluation Models in Physical Education Learning: Systematic Literature review - Hasyim, Andi Hasriadi; Haris, Iyan Nurdiyan; Yulianto, Ari Gana (Indonesian Journal of Sport Management, 2024)
Knowledge about evaluation has an important role in overcoming various problems in physical education learning. There are various types of program evaluation models used, and therefore, the aim of this research is to explore and review the application of various program evaluation models that have been carried out in the context of physical education learning. The method used in this research is a literature review. Data was collected from three database sources, namely Google Scholar, Garuda Ristekdikti, and Sinta Journal, using the keywords "program evaluation model" and "physical education". The time span of this research covers the period 2018 to 2022. Data search results show as well as 6 articles from Google Scholar, 1 article from Garuda Ristekdikti, and 8 articles from Sinta Journal, so a total of 15 articles will be analyzed. Based on the research results, it appears that the CIPP evaluation model is more popular and is often used to evaluate physical education learning programs, and this evaluation is generally carried out at the secondary school level.